Biological control of the eucalypt borers, Phoracantha semipunctata (Fabricius) and P. recurva Newman (Coleoptera: Cerambycidae) in South Africa - Moore, Judy A. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.